2019
DOI: 10.1111/gcb.14832
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial trends in marine carbon isotopes in the Arctic Ocean and implications for food web studies

Abstract: The Arctic is undergoing unprecedented environmental change. Rapid warming, decline in sea ice extent, increase in riverine input, ocean acidification and changes in primary productivity are creating a crucible for multiple concurrent environmental stressors, with unknown consequences for the entire arctic ecosystem. Here, we synthesized 30 years of data on the stable carbon isotope (δ13C) signatures in dissolved inorganic carbon (δ13C‐DIC; 1977–2014), marine and riverine particulate organic carbon (δ13C‐POC; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 109 publications
4
54
0
Order By: Relevance
“…This ratio is widely applied in trophic food web analyses, but the basis for its specific use to contrast sea ice algae vs. phytoplankton is the relative shortage of inorganic carbon for photosynthesis in spatially limited brine channels where high biomass densities might accumulate, as opposed to a usually well replenished surface layer of the ocean. As a result, δ 13 C values in sympagic algae become enriched over time by 13 C. A strong impact of both nutrient availability as well as taxonomic composition on sympagic particulate organic carbon (POC) δ 13 C was described previously [28], and the implications for tracing the fate of ice algal production in Arctic food webs is discussed extensively both in this work, as well as more recently [29]. One caveat of this approach is that Arctic phytoplankton can also exhibit considerable base-line variation in its isotope values which can result in overlaps with sea ice algae, complicating foodweb analyses [30].…”
Section: Carbon Stable Isotope Ratios (δ 13 C)mentioning
confidence: 82%
See 1 more Smart Citation
“…This ratio is widely applied in trophic food web analyses, but the basis for its specific use to contrast sea ice algae vs. phytoplankton is the relative shortage of inorganic carbon for photosynthesis in spatially limited brine channels where high biomass densities might accumulate, as opposed to a usually well replenished surface layer of the ocean. As a result, δ 13 C values in sympagic algae become enriched over time by 13 C. A strong impact of both nutrient availability as well as taxonomic composition on sympagic particulate organic carbon (POC) δ 13 C was described previously [28], and the implications for tracing the fate of ice algal production in Arctic food webs is discussed extensively both in this work, as well as more recently [29]. One caveat of this approach is that Arctic phytoplankton can also exhibit considerable base-line variation in its isotope values which can result in overlaps with sea ice algae, complicating foodweb analyses [30].…”
Section: Carbon Stable Isotope Ratios (δ 13 C)mentioning
confidence: 82%
“…This is in agreement with other studies, which identified phytoplankton growth rate, as well as the availability of carbon, light, and nutrients to affect isotopic fractionation and the δ 13 C-POM values. In addition to these biological factors, there are also temporal and regional differences in the δ 13 C baseline in inorganic carbon [29] which also affect δ 13 C in POM. Thus, even the baseline signal in sea ice might undergo a pronounced temporal variation, and thereby also contribute to the high variability in δ 13 C-POC ice .…”
Section: Stable Isotope Ratios In Bulk Pom and Specific Fatty Acidsmentioning
confidence: 99%
“…The δ 13 C Phe of Atlantic walrus in Foxe Basin declined at a rate of 0.6‰ per decade from 1982 to 2016 in association with a decreasing sea ice concentration and earlier sea ice breakup, and was 0.8‰ lower in 2006 than in 1996 in Jones Sound, suggesting less sea ice-derived carbon in the benthos over time in both areas which aligns with our H-Print estimates. The decadal declines of δ 13 C Phe in Atlantic walrus from both study areas is six to eight times higher than the decrease of δ 13 C of dissolved inorganic carbon in Arctic marine waters (−0.11‰ per decade) attributed to increasing concentrations of anthropogenic CO 2 in the atmosphere known as the Suess effect [ 47 ]. Additionally, our decadal declines in δ 13 C Phe parallel estimates from [ 47 ] where the entire pool of δ 13 C of particulate organic carbon in the Arctic Ocean decreased by 0.6‰ per decade with declining sea ice in combination with increased phytoplankton primary productivity [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between δ 13 C and benthic standing stock is less obvious, especially in this study, where we reported higher standing stock in fjords characterized by lower δ 13 C values. Depleted δ 13 C is usually interpreted as indicating a higher contribution of terrestrial or partially decomposed organic matter 54,55 . In the studied locations δ 13 C was higher in northern Norway fjords (low precipitation and terrestrial inflows) than in southern Norway (high precipitation and dense land vegetation) and Svalbard (glacial erosion) 56 .…”
Section: Discussionmentioning
confidence: 99%